FACTORIAL DESIGN, OPTIMIZATION OF SWEETSOP STARCH AS A NEW NATURAL SUPERDISINTEGRANT IN THE FORMULATION OF CARVEDILOL FAST DISSOLVING TABLETS FOR BIOAVAILABILITY ENHANCEMENT - DEVANI, RAMA CHAKRADHAR; RADA, SANTOSH KUMAR (International Journal of Applied Pharmaceutics, 2025)
Objective: Carvedilol is a BCS class-II nonselective cardiac beta blocker with low bioavailability (35%) due to its poor solubility. To enhance the solubility and bioavailability, it can be formulated in Fast Dissolving Tablets (FDTs) employing a new natural superdisintegrant, Sweetsop starch, through factorial design. Methods: Sweet Sop Starch (SSS) was extracted from the pulp of Annona squamosal L. The micromeritics characteristics of SSS were assessed, and the resulting product was utilized as a new superdisintegrant in the direct compression method of formulating Carvedilol (CRV) FDTs. The SSS was evaluated employing Fourier-transform infrared spectroscopy (FTIR), powdered x-ray diffraction, differential scanning calorimetry, and scanning electron microscopy. SSS, Potato starch (PS), and Sodium Starch Glycolate (SSG) were employed as superdisintegrants, and factorial design was used to investigate their disintegration property, Wetting Time (WT), and in vitro dissolution. The hardness, friability, homogeneity of Drug Content (DC), Water Absorption Ratio (R), in vivo pharmacokinetics, and stability parameters of formulated carvedilol FDTs were assessed. Results: Micromeritic characteristics revealed that the produced SSS was fine, free-flowing, and crystalline. FTIR and DSC investigations indicated that there were no drug-excipient interactions. From the prepared formulations (F1 to F8), the one with a 5% SSS containing formulation CF2, demonstrated 98.44±1% drug release within ten minutes with 45±0.11 sec WT and had 32±01 sec DT. The optimized formula attained peak plasma concentration extremely quickly and showed 176.11 % relative bioavailability. Conclusion: The formula containing 5% SSS showed good mechanical and physical characteristics, increased drug dissolution, and promoted quick disintegration with enhanced relative bioavailability in the management of hypertension and patient acceptance.